Cost and affordability of the food basket in the Republic of Moldova - Siminiuc, Rodica; Țurcanu, Dinu; Siminiuc, Sergiu (Frontiers in Sustainable Food Systems, 2025)
IntroductionFood and nutrition security remain among humanity's most urgent challenges, with 23.5% of Moldova's population experiencing food insecurity. Despite the critical nature of this issue, national-level research on nutritional security remains scarce. This study aims to evaluate the cost and accessibility of minimum consumption and healthy food baskets in Moldova to better understand affordability constraints and inform policy interventions.MethodsThe study assesses the cost and affordability of food baskets by calculating their cost as a proportion of the country's minimal subsistence amount and evaluating affordability using the International Poverty Line (IPL) criterion. The analysis focuses on two key food baskets: the Minimum Consumption Food Basket (MCFB) and the Healthy Food Basket (HFB).ResultsFindings indicate that 52% of the population lacks access to the MCFB, while 78.6% cannot afford the HFB without reallocating non-food expenses. Affordability gaps were most pronounced among lower-income households, highlighting significant vulnerabilities within specific socio-demographic groups.DiscussionThese results underscore the urgent need for policies addressing food affordability and accessibility in Moldova. Strengthening national strategies to align with Sustainable Development Goals (SDGs) 2 (Zero Hunger) and 3 (Good Health and Wellbeing) could help mitigate food insecurity risks. By addressing affordability gaps and ensuring equitable access to nutritious food, these strategies can support national development priorities and enhance food security resilience.